Atomic‐Level Insight into the Formation of Subsurface Dislocation Layer and Its Effect on Mechanical Properties During Ultrafast Laser Micro/Nano Fabrication. (23rd November 2021) - Xie, Jiawang; Yan, Jianfeng; Zhu, Dezhi; He, Guangzhi
Abstract: Micro/nano processing technologies have been extensively studied since micro/nano structures are used in different area such as microelectronics and microdevices. As a high‐precision processing technology, ultrafast laser has been applied in the fabrication of different types of metallic micro/nano structures. However, the knowledge about the materials response of metals at atomic scale during laser processing is still necessary to explore. Herein, the femtosecond laser processing of metals from the atomic structure perspective is revealed. Three different layers named recast layer, high density dislocation layer, and unaffected layer are found after femtosecond laser irradiation. The recast layer is on the surface, which is generated from the resolidification of melting materials. The high density dislocation layer, consisting of dislocations and stacking faults, is observed beneath the irradiated surface. The dislocation layer is produced by the laser‐induced stress wave, and the mechanical properties of irradiated surface are affected by the laser‐induced subsurface dislocation layer. The unaffected layer is not affected by laser irradiation, and maintains the initial atomic structure. The research gives new information about the ultrafast laser processing of metals at atomic‐level, which is helpful to the fabrication of functional micro/nano devices for wide applications. Abstract : As a high‐precision technology, ultrafast laser fabrication is applied in manufacturing functional micro/nano devices. This study reveals the atomic structure evolution of metal during ultrafast laser fabrication. Three layers named recast layer, dislocation layer, and unaffected layer are formed after laser irradiation, and the mechanical properties of metal are affected by the laser‐induced dislocation layer.